2007
DOI: 10.1203/pdr.0b013e31805365db
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Volume and Anisotropy in Preterm Children: A Pilot Study of Neurocognitive Correlates

Abstract: ABSTRACT:The objectives of this study were to evaluate the differences in whole brain white matter (WM) volume and anisotropy between preterm and term children and to determine the relationships with cognitive outcome. Twenty-five low birth weight (BW), preterm, neurologically normal children between 8.8 and 11.5 y of age were recruited for volumetric and diffusion-tensor magnetic resonance imaging (DTI), together with 13 age-matched term control subjects. Subsequent intelligence quotient (IQ) testing was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 52 publications
(53 reference statements)
3
55
1
1
Order By: Relevance
“…Studies of preterm born children in late childhood also demonstrate significantly reduced FA in various WM tracts. Mean FA values of the whole WM of the brain was significantly decreased in preterm born children at the age of 8-11 years (Yung et al, 2007), and widespread decreases in FA was found in the uncinate fasciculus, the inferior and superior fronto-occipital fasciculus, splenium of corpus callosum, and the external capsule in preterm born children at the age of 12 (Constable et al, 2008). In the current VLBW group decreased FA was shown at 15 years in large WM areas, including the posterior part of cingulum, occipital periventricular WM, superior longitudinal fasciculus, arcuate fasciculus, corpus callosum and capsula interna (Vangberg et al, 2006).…”
Section: Reduced Fa In the Vlbw Groupmentioning
confidence: 89%
See 1 more Smart Citation
“…Studies of preterm born children in late childhood also demonstrate significantly reduced FA in various WM tracts. Mean FA values of the whole WM of the brain was significantly decreased in preterm born children at the age of 8-11 years (Yung et al, 2007), and widespread decreases in FA was found in the uncinate fasciculus, the inferior and superior fronto-occipital fasciculus, splenium of corpus callosum, and the external capsule in preterm born children at the age of 12 (Constable et al, 2008). In the current VLBW group decreased FA was shown at 15 years in large WM areas, including the posterior part of cingulum, occipital periventricular WM, superior longitudinal fasciculus, arcuate fasciculus, corpus callosum and capsula interna (Vangberg et al, 2006).…”
Section: Reduced Fa In the Vlbw Groupmentioning
confidence: 89%
“…These micro-structural differences are mainly seen as reductions in FA in central WM regions at term equivalent age (Hüppi et al, 2001). These changes persist through childhood and into adolescence (Anjari et al, 2007;Bassi et al, 2008;Constable et al, 2008;Nagy et al, 2003;Partridge et al, 2004;Rose et al, 2008;Vangberg et al, 2006;Yung et al, 2007). The effects of being born preterm on WM in early adulthood remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the preterm infants had MDI scores within the normal range, similar to the term infants. Cognitive function may have been underestimated in the present study because the assessment of cognitive function was performed at an earlier age than in previous studies [22,23], therefore the diagnosis may be limited [24]. Postnatal infection and chronic lung disease are known risk factors for poor neurodevelopmental outcomes [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…13 The CC thickness may be secondarily affected by fibre loss, 12 as seen in children after severe hypoxic ischaemic injury, HIV encephalopathy or large infarcts.…”
Section: Discussionmentioning
confidence: 99%